Axial-schwinger model - Amorim, R.; Barcelos-Neto, J.; Dutra, Alvaro de Souza [UNESP] (World Scientific Publishing, 1996)
We consider an extension of the axial model where local gauge symmetries are taken into account. The result is a mixing of the axial and Schwinger models. The anomaly of the axial current is calculated by means of the Fujikawa path integral technique and the model is also solved. Besides the well-known features of the particular models (axial and Schwinger) an effective interaction of scalar and gauge fields via a topological current is obtained. This term is responsible for the appearance of massive poles in the propagators that are different from those of both models.